2015
DOI: 10.1016/j.cortex.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Resting BOLD fluctuations in the primary somatosensory cortex correlate with tactile acuity

Abstract: Sensory perception, including 2-point discrimination (2ptD), is tightly linked to cortical processing of tactile stimuli in primary somatosensory cortices. While the role of cortical activity in response to a tactile stimulus has been widely investigated, the role of baseline cortical activity is largely unknown. Using resting state fMRI we investigated the relationship between local BOLD fluctuations in the primary somatosensory cortex (the representational field of the hand) and 2ptD of the corresponding ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
(67 reference statements)
2
21
0
Order By: Relevance
“…Namely, accurate sensorimotor functions require a precision of neural representation with surrounding nonspecific activities suppressed. A recent rfMRI study in healthy individuals has shown that higher local signal amplitude and synchronicity in the somatosensory cortex, measured with fALFF and ReHo respectively, are related to better tactile discrimination abilities [Haag et al, 2015]. Based on this report, the present observation of decreased ReHo in the postcentral gyrus may also reflect impaired surround inhibition in individuals with CD suggesting impaired ability of proper control of agonist and antagonist muscles involved in head movements.…”
Section: Discussionsupporting
confidence: 68%
“…Namely, accurate sensorimotor functions require a precision of neural representation with surrounding nonspecific activities suppressed. A recent rfMRI study in healthy individuals has shown that higher local signal amplitude and synchronicity in the somatosensory cortex, measured with fALFF and ReHo respectively, are related to better tactile discrimination abilities [Haag et al, 2015]. Based on this report, the present observation of decreased ReHo in the postcentral gyrus may also reflect impaired surround inhibition in individuals with CD suggesting impaired ability of proper control of agonist and antagonist muscles involved in head movements.…”
Section: Discussionsupporting
confidence: 68%
“…The increased VMHC under heat stress probably reflects the thermal sensation of the body, as a recent animal study has revealed that stress increases connectivity within the somatosensory networks [37]. In addition, the primary somatosensory cortex activity correlates with sensory perception and task performance [38,39]. As we did not measure sensory perception and task performance in the current study, the correlation between VMHC of the primary somatosensory cortex activity and sensory perception or task performance under heat stress needs to be explored in future studies.…”
Section: Vmhc Of Resting Statementioning
confidence: 97%
“…Then spatial smoothing was performed on the standardized individual ReHo map with a Gaussian kernel of 4 mm full-width at half maximum (FWHM) (21). After the preprocessing, fALFF were computed as previously described (11,14). First, the resampled images were smoothed with a Gaussian kernel of 4 mm.…”
Section: Image Processingmentioning
confidence: 99%
“…The spontaneous local brain activity can be quantitatively measured by regional homogeneity (ReHo) (9,10) and fractional amplitude of the low frequency fluctuations (fALFF) (11,12). Both of them are powerful and reliable indices in evaluating resting-state brain activity (13)(14)(15). ReHo was first proposed by Zang et al (9).…”
mentioning
confidence: 99%